AB0784 Myocardial fibrosis detected by magnetic resonance imaging in systemic sclerosis—pathophysiological significance. (12th June 2018) - Funauchi, M.; Kishimoto, K.; Nozaki, Y.
Abstract : Background: Systemic sclerosis (SSc) is characterised by chronic fibrosis in various organs such as skin, lung and heart leading to poor prognosis. Myocardial fibrosis is one of factors of pulmonary hypertension (PH) as well as pulmonary arterial hypertension or interstitial lung disease (ILD). Detection of cardiac lesions has progressed much using imaging techniques such as echocardiography (UCG) in combination with measurement of various biomarkers such as BNP. Recently, cardiac magnetic resonance imaging (CMR) has been shown to be sensitive to detect even subclinical cardiac lesions. However, it is unclear what subtype of SSc is prone to myocardial fibrosis, when it manifests in the clinical course, or whether fibrosis occurs simultaneously in various organs. Objectives: To clarify the pathophysiological significance of myocardial fibrosis in SSc, CMR was performed in the patients with limited (lc) and diffuse (dc) cutaneous SSc with or without PH. Methods: Twelve patients (male 2, female 10) who fulfilled ACR/ EULAR criteria (2013) for SSc were enrolled. Eight patients were diagnosed as having lcSSc and 4 dcSSc. In addition to CMR, chest CT scan, UCG and laboratory tests including serum autoantibodies specific for SSc, blood brain natriuretic peptide (BNP) and pulmonary function test (%FVC, %DLCO) were performed in all patients. Right heart catherization was performed in patients whose systolic right ventricular pressure estimated by UCG was higher than 30 mmHg. Positivity of late gadolinium enhancement (LGE) was compared with clinical findings and these parameters. Difference between the patient groups were tested using Student's t-test. Results: LGE was positive in 6 out of 12 patients. Patient composition of dc/lc in LGE (+) and LGE (-) group was 1/5 and 3/3, respectively. Complication of ILD was present in 3 among LGE (-) patients, while esophageal involvement in 3 among LGE (+) patients. The mean age of LGE (+) group tended to be higher than that of LGE (-) group (73.8±5.8 vs 68±6.4), duration of disease (year) tended to be shorter in LGE (+) group than those of LGE (-) group (1.8±3.0 vs 7.7±5.5), and BNP level (170.6±150.1 vs 90.1±69.0 pg/ml) and RVP (33.5±8.1 vs 29.7±8.1 mmHg) tended to be higher in LGE (+) than in LGE (-) group, although difference was not statistically significant. There was no tendency of positivity of autoantibodies and pulmonary function test, while patients with low%DLCO (<70) and without ILD were positive for LGE. LGE tended to be positive in the patients whose E/e' ratio determined by UCG or pulmonary capillary wedge pressure by RHC was elevated. Conclusions: Since myocardial fibrosis was found rather in the cases without ILD, there might be difference in the progression of fibrosis depending on the organ, although it accelerates by ageing. If LGE is seen, PH, especially that associated with left heart disease, might occur in future. This study suggests that CMR might be useful to detect cardiac lesions from early period of clinical course, as well as in the cases with some abnormalities in biomarkers such as BNP or DLCO regardless of existence of ILD, although further study is needed to clarify the indication of CMR using more cases of SSc. Disclosure of Interest: None declared